What Does This Story Say About Females?: Challenging Gender‐Biased Texts in the English‐Language Classroom. Issue 4 (21st July 2015) - Hayik, Rawia
Abstract: Grounded in critical literacy theory, this teacher research in a Middle Eastern EFL classroom addresses the traditional female positioning in literature, media, and pop culture. Adolescent students are encouraged to challenge the traditional Cinderella fairy tale through various critical literacy engagements. A content analysis of sample written and oral responses against the four dimensions framework of critical literacy reveals emerging critical awareness of gender bias and eagerness to take action for change, basically on the part of female students who wrote challenging letters of critique to the author of a Disney‐fied version of the story. Scrutiny into the teacher's moves attempts to explore her role in the process.